Changes in Running Economy During a 65-km Ultramarathon - Scheer, Volker (Front Physiol, 2018)
Purpose: Running economy (RE), expressed as oxygen cost (O(2) cost) and energy cost of running (Cr) is important in ultramarathon (UM) running as it can help predict race performance. Controversy remains if RE increases, decreases, or remains stable in UM running. We examined RE before, during, and after a 65-km UM. Methods: 15 male UM runners (mean age 45 ± 5.7 years) completed a standard exercise test (mean VO(2)max 48.8 ± 3.4 ml⋅kg(-1)⋅min(-1)) for determination of the individual testing speed (60% VO(2)max: mean speed 9.4 ± 0.7 km/h). This was followed by a 65-km UM (elevation ± 1093 m) consisting of three laps (each 21.7 km). Pre and post indirect calorimetry measurements at individual running speed on the treadmill at UM-specific slopes (average percentage of positive and negative elevation) at -3, +3%, and level grade were performed in randomized order on a motorized treadmill in the laboratory for calculation of RE. Additionally after each lap, testing at +3% took place. Results: The O(2) cost, Cr, and RER increased significantly pre to post UM (p < 0.01). During the uphill running, a main effect of distance indicated a gradual, linear increase in O(2) cost, F(2,28) = 5.81, p < 0.01, [Formula: see text] = 0.29, and Cr, F(2,28) = 5.96, p = 0.01, [Formula: see text] = 0.30. Conclusion: O(2) cost and Cr increased significantly pre to post UM in all testing conditions as well as during the uphill testing throughout the UM. This is the first study to demonstrate a consistent increase in O(2) cost and Cr among a range of different slopes, at individual running speeds and race-specific slopes giving further evidence that these measures of RE increase in UM running.